China's rural labor migration and its economic development - Liu, Xiaoguang 1988- (World Scientific, 2020)
"The continuous migration of rural labor to cities has changed the fundamental characteristics of China's labor market, profoundly affected the country's investments, savings, technological progress and economic cycle fluctuation, and more importantly, the rapid development of non-agricultural industries. Though the significant changes in China's labor market has played a vital role in the country's economic growth, it has not been duly valued and studied. This book aims to fill the gap by studying the role of rural labor in China's economic development. The book systematically presents the three most important characteristics of China's economic development and summarizes them as "the riddle of China's rising return on capital", "the riddle of China's rising rate of saving", and "the riddle of 'Okun's law' not applicable to China". It empirically and theoretically analyses the "three riddles" from the perspective of the migration of rural labor. It also proposes macro-policies and developmental strategies to address the "three riddles"."
Aus dem Chinesischen übersetzt
Includes bibliographical references and index
Keywords: Wirtschaftsentwicklung; Arbeitsmarkt; Landarbeiter; Verstädterung; Migration; China; Landflucht / (DE-627)091373905 / (DE-STW)10504-1; Arbeitsmigranten / (DE-627)091348838 / (DE-STW)11268-3; Agrarberufe / (DE-627)091374324 / (DE-STW)11276-4; Ländlicher Arbeitsmarkt / (DE-627)091374049 / (DE-STW)19462-2; Arbeitsmarkt / (DE-627)091347572 / (DE-STW)11183-4; Entwicklung / (DE-627)091357322 / (DE-STW)10513-0; China / (DE-627)091353777 / (DE-STW)17565-2; Labor market / China; Migrant labor / China; Rural-urban migration / China; Economic development / China